Implementasi Kebijakan Pengelolaan Sampah dan Dampaknya terhadap Masyarakat: Studi Kasus Blokade Warga Jatirejo di Kota Surakarta - Farrel Rama Dhitya Densen; Apriando Reubben Patrick; Ester Saur Maulina Sinaga; Abel Nafa Erfatiana; Anisa Ramadhani; Nur Achmad Faisal; Alya Maya Khonsa Rahayu (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2026)
This research intends to examine how waste management policies are carried out and their effects on the local community in Surakarta City, focusing on the blockade actions by Jatirejo residents near the Putri Cempo Landfill. The approach taken is empirical juridical research utilizing both a legislative angle and a case study perspective. Information was collected through literature reviews and documentation, which were then analyzed descriptively and qualitatively. Findings from the research reveal that the execution of waste management policies is not functioning effectively, even though there are regulations in place, such as the Decree of the Mayor of Surakarta Number 600.4.15/138 of 2025 and Circular Letter Number 25 of 2005 about waste separation. Key issues include inadequate facilities and infrastructure, poor coordination, and ineffective communication between the government and residents. The burdened state of the landfill leads to various environmental issues like air contamination, possible waste landslides, and health concerns for the public. Additionally, social consequences manifest as conflicts, highlighted by residents’ blockade actions as they protest against worsening environmental conditions.